A 6.55 factor primal-dual approximation algorithm for the connected facility location problem - Jung, Hyunwoo; Hasan, Mohammad Khairul; Chwa, Kyung-Yong (Journal of combinatorial optimization, 2009)
In the connected facility location (ConFL) problem, we are given a graph G =( V , E ) with nonnegative edge cost c e on the edges, a set of facilities ℱ⊆ V , a set of demands (i.e., clients) , and a parameter M ≥1. Each facility i has a nonnegative opening cost f i and each client j has d j units of demand. Our objective is to open some facilities, say F ⊆ℱ, assign each demand j to some open facility i ( j )∈ F and connect all open facilities using a Steiner tree T such that the total cost, which is , is minimized. We present a primal-dual 6.55-approximation algorithm for the ConFL problem which improves the previous primal-dual 8.55-approximation algorithm given by Swamy and Kumar (Algorithmica 40:245–269, 2004 ).